Automatic Medical Assistance with Dynamic Tele Monitoring System - S. Francis Shamili; Aadith H; Vivek Kumar; Tamil Azhagan; Jovakwin Litinov (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The optimization of our wearable assist system (AS) to monitor isolated patients on isolation wards. A wearable chest patch and finger-worn pulse oximeter were used to estimate and transmit continuous temp, Heart Rate (HR), and peripheral blood Oxygen Saturation (SpO2) data from ambulatory patients on these isolation wards to nurse bays remote from these patients, with a view to minimizing the risk of infection for nursing staff. Our virtual High-Dependency Unit system used a secure web-based architecture and protocols to transmit the vital-sign data in real time from wireless Android tablet devices, operating as patient data collection devices by the bedside in the isolation rooms, into the clinician dashboard interface Available nremotely via any modern web- browser. Although Internet of Things buttons have seen some success as consumer products, little has been reported on their application in hospital systems. The system can be used to check the health condition of the patient by using three sensor such as heart beat sensor, temperature sensor and pressure sensor and also to monitor the saline droplet condition of patients in each patient’s bed in rural public hospital. Therefore, a particular interest is focused on continuous monitoring techniques. For continuous monitoring, Atmega328 microcontroller is used. In this case several sensor unit is considered. the sensed value is equal to normal value, it stops further process. Otherwise it sends control signals to patient via Actuator.